Temporal effects in glare response - Kent, Michael G. (2016)
Discomfort glare is considered to be an annoyance or distraction caused by sources of non-uniform or high luminance within the field of view of an observer. There are still significant gaps in our understanding of the conditions that characterise the magnitude and occurrence of discomfort glare, this being especially evident in the presence of large sources of luminance such as windows. The large degree of scatter that is observed when subjective evaluations of glare sensation are compared against calculated glare indices suggests that discomfort glare may be dependent on other variables beyond the physical and photometric parameters that are commonly embedded in glare formulae (e.g., source luminance, source size, background luminance, and position index). There are strong reasons to believe that some of these variables might be linked to the time of day when the observer is exposed to the glare source. In response, this thesis investigated the research hypothesis that subjective glare sensation is associated with temporal variability. This hypothesis was tested in two stages. The first stage was conducted within a laboratory setting, and sought to examine temporal effects under controlled artificial lighting conditions. The collection of temporal variables and personal factors – thereby examining the scatter in glare responses across the independent variable (time of day) and isolating potential confounding variables – enabled to identify factors that could influence the subjective evaluation of glare sensation along the day. Having established the presence of a temporal effect on glare response, the influences detected were further explored within a test room with direct access to daylight, whereby temporal variables and personal factors were measured in conjunction to glare sensation for them to be statistically masked from the analysis. The results confirmed the hypothesis of an increased tolerance to glare as the day progresses. This supported the conclusion that physical and photometric parameters alone are not sufficient for a robust prediction of discomfort glare.